The Effect of Abortion Policies on Fertility and Human Capital in Sub-Saharan Africa - Arcangelo Dimico (Queen's University Belfast, Queen's Business School, 2024)
I evaluate the impact of abortion policies in sub-Saharan Africa to understand possible consequences from a reduced international support for women's rights following the overturn of Roe v. Wade. I find that decriminalizing abortion reduces fertility through two complementary channels. For households at the top of the wealth distribution, the effect manifests as a reduction in excess fertility, which is more pronounced among lower-educated women due to their lower likelihood of using contraception. For households at the bottom of the wealth distribution, the impact runs through a decline in the number of children with a low survival probability. This latter effect is more pronounced among highly educated women, who are more likely to control their own health-related decisions and view abortion as a viable option. I also find that while women's education levels rise after decriminalization, this does not lead to better labor market opportunities. However, children born afterward tend to achieve higher levels of education.
Keywords: O15; L1; J13; J16; K38; 330; Abortion; fertility; child mortality; human capital